Between Innovation and Tradition: Teachers’ and Students’ Perceptions of Artificial Intelligence (AI) in Pesantren English Classrooms - M. Adib Nazri; Made Hery Santosa; Ni Made Ratminingsih; Yulia Agustina (Journal of Educational Studies, 2026)
This study explores the perceptions, pedagogical challenges, and integration strategies of teachers and students regarding the use of Artificial Intelligence (AI) in English language classrooms within a pesantren (Islamic boarding school) context. Employing a case study design with a phenomenological lens, this research aims to uncover how AI-based tools are received and interpreted amidst the daily learning experiences of a single pesantren. Data are collected through semi-structured interviews and reflective observations, while acknowledging the researcher’s dual positionality as both an insider and observer to ensure a nuanced interpretation of the findings. The study focuses on both the pedagogical benefits and the cultural tensions between technological innovation and traditional religious values. The findings are expected to offer a framework for culturally responsive AI integration in language education, specifically contributing to the discourse of digital literacy within Islamic educational settings